25 MeV solar proton events in Cycle 24 and previous cycles. Issue 4 (15th August 2017) - Richardson, Ian G.; von Rosenvinge, Tycho T.; Cane, Hilary V.
Abstract: We summarize observations of around a thousand solar energetic particle (SEP) events since 1967 that include ∼25 MeV protons, made by various near-Earth spacecraft (IMPs 4, 5, 7, 8, ISEE 3, SOHO), that encompass Solar Cycle 20 to the current cycle (24). We also discuss recent observations of similar SEP events in Cycle 24 made by the STEREO spacecraft. The observations show, for example, that the time distribution of ∼25 MeV proton events varies from cycle to cycle. In particular, the time evolution of the SEP occurrence rate in Cycle 24 is strongly asymmetric between the northern and southern solar hemispheres, and tracks the sunspot number in each hemisphere, whereas Cycle 23 was more symmetric. There was also an absence of 25 MeV proton events during the solar minimum preceding Cycle 24 (other minima show occasional, often reasonably intense events). So far, events comparable to the exceptionally intense events detected in Cycles 22 and 23 have not been observed at Earth in Cycle 24, though Cycle 21 (the largest of the cycles considered here) also apparently lacked such events. We note a correlation between the rates of intense 25 MeV proton events and "ground level enhancements" (GLEs) observed by neutron monitors, since 1967, and conclude that the number of "official" GLEs (1) observed to date in Cycle 24 appears to be significantly lower than expected (5 to 7 ± 1) based on the rate of intense 25 MeV proton events in this cycle.